Epidemiology and Molecular Characteristics of Mycoplasma pneumoniae During an Outbreak of M. pneumoniae-associated Stevens-Johnson Syndrome. Issue 6 (June 2017) - Watkins, Louise K. Francois; Olson, Daniel; Diaz, Maureen H.; Lin, Xia; Demirjian, Alicia; Benitez, Alvaro J.; Winchell, Jonas M.; Robinson, Christine C.; Bol, Kirk A.; Glodé, Mary P.; Dominguez, Samuel R.; Miller, Lisa A.; et al.
Abstract : Background: An increase in Mycoplasma pneumoniae -associated Stevens-Johnson syndrome (SJS) cases at a Colorado pediatric hospital led to an outbreak investigation. We describe the epidemiologic and molecular characteristics of M. pneumoniae among SJS case-patients and surrounding community members during the outbreak. Methods: M. pneumoniae polymerase chain reaction-positive respiratory specimens from 5 Colorado hospitals and 4 referral laboratories underwent confirmatory polymerase chain reaction testing; positive specimens then underwent multilocus variable-number tandem-repeat analysis (MLVA) and macrolide resistance testing. Three SJS- M. pneumoniae case-patient households were surveyed using a standardized questionnaire, and nasopharyngeal/oropharyngeal swabs were obtained from all consenting/assenting household contacts. International Classification of Diseases, 9th revision codes were used to identify pneumonia cases among Colorado patients 5–21 years of age from January 2009 to March 2014. Results: Three different M. pneumoniae MLVA types were identified among the 5 SJS case-patients with confirmed infection; MLVA type 3-X-6-2 was seen more commonly in SJS case-patients (60%) than in 69 non-SJS community specimens (29%). Macrolide resistance was identified in 7% of community specimens but not among SJS case-patients. Of 15 household contacts, 5 (33%) were M. pneumoniae positive; all MLVA types were identical to those of the corresponding SJS case-patient, although the specimen from 1 contact was macrolide resistant. Overall pneumonia cases as well as those caused by M. pneumoniae specifically peaked in October 2013, coinciding with the SJS outbreak. Conclusions: The outbreak of M. pneumoniae -associated SJS may have been associated with a community outbreak of M. pneumoniae ; clinicians should be aware of the M. pneumoniae –SJS relationship. Household transmission of M. pneumoniae was common within the households investigated.